Xylem Limited Bacteria (XLB) Clove Disease Control Technology Through Utilization of Endophytic Bacteria - Chrisnawati, Chrisnawati; Nasrun, Nasrun; Yulfidesi, Yulfidesi; Suryani, Suryani; Kasmawati, Kasmawati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
Xylem Limited Bacterium (XLB) disease (Ralstonia syzygii) is the most seriuos disease on clove plant. Biological control using Endophytic Bacteria (Bacillus sp. Bc25 and Fluorescentpseudomonad Pf22) is expected to control clove XLB disease.The research aim to get Bacillus sp. Bc25 and Fluorescent pseudomonad Pf22product are effective to control XLB disease on clove plant.The study of Bacillus sp. Bc25 and Fluorescent pseudomonad Pf22 was done in watering on clove plant field were infected by XLB disease in Solok West Sumatera on January to December 2017.The study used a randomized block design (RBD) with four replications. The parameters observed were the disease attack level and plant growth.The study results showed thatBacillus sp.Bc25 andFluorescentpseudomonadPf 22 can control XLB disease and increase clove growth.Bacillus sp. Bc25 and Fluorescentpseudomonad Pf22 combinationdemonstrate XLB disease control capabilities and promote the best clove plants growthby intensity suppressing of XLB disease from 86.80% to 20.59% and increasing the clove plants growth from the stem circle 20.00 cm to 46.00 cm.Combination product of biological agents Bacillus sp. Bc25 and FluorescentpseudomonadPf22 can be developed to control XLB diseases and increase clove plant growth.Keywords : Clove, Xylem Limited Bacteria Disease (Ralstonia syzygii), Endophytic Bacteria (Bacillus sp. Bc25 and Fluorescent pseudomonad Pf22.